Microwave nondestructive testing of textile and composite materials using free-space microwave measurement system / Jamil Salleh ... [et al.] - Salleh, Jamil; Ghodgaonkar, Deepak Kumar; Wan Ahmad, Wan Yunus; Mohd Tamyis, Najihah (2002)
Textile-reinforced composites play an important role in the advancement of the aeronautics and aerospace industries. The success results from the ability to make use of the outstanding strength, stiffness and low gravity of fibers such as glass, graphite or Kevlar. In this research, microwave nondestructive testing techniques (MNDT) such as reflection, transmission and dielectric measurements will be applied to characterize some of the properties of textile composites in a frequency range of 8 to 12.5 GHz.. The free-space microwave measurement system (FSSM) consists of a pair of spot- focusing horn lens antennas, a vector analyzer, mode transitions and a computer. We have measured textiles composites made from different types of fibers such as Kevlar, spectra, S-glass and fiberglass with different types of resins such as vinylester, phenolic and epoxy. These composites have different weave patterns such as plain, satin, 2x2 basket and non-woven stitch. Experimental results are reported for dielectric constants and loss tangents of these materials.